Nursing laboratory and critical education of nurses: approaches and distances - Fatima Maria de Melo Brito; Célia Alves Rozendo; Priscila de Oliveira Cabral Melo
ABSTRACT Objective: to analyze the contribution of the laboratory of nursing to the critical education of nurses. Method: qualitative study, conducted among 18 professors of higher education institutions, being one public and the other private. Data were collected between February and November of 2016 by means of semi-structured interview. To analyze data, it was used a content analysis in the thematic modality. Results: it was observed the emphasis in the technical skills development by propagation of behavior and practices; the creation of bonds between professors and students happens on the limit of good interpersonal relationship; the laboratory of nursing may help the critical reflection about the practice, being a place that allows the learning of ethics. Final considerations: the nurse education, carried out by the laboratory of nursing, have to overcome the emphasis in the uncritical reproduction of practices and to observe the nurse's power to think about the reality in the meaning of its modification.